A study on factors affecting affective organizational commitment among knowledge workers in Malaysia - Govindasamy, Muhiniswari; Jayasingam, Sharmila (2010)
Knowledge management (KM) has been often claimed to be an essential ingredient in building competitive advantage.One of the biggest challenges for most knowledge organizations in these highly competitive times comes from changes in work behaviours of knowledge workers.Understanding knowledge workers and what makes them stay and continue to contribute to the organization is a formidable task for most managers.Thus, the nature of this study is to determine the factors which will influence affective organizational commitment among knowledge workers.This research will contribute significantly to organizations wanting to encourage knowledge workers to be committed and continue their service with them in this knowledge–based economy.